Strategi Guru PAI Dalam Membentuk Pendidikan Karakter Siswa Di MTSN 2 Cianjur - Zaenudin, Miftah; Na’imah, Farida Ulvi; Kholis, Mohammad Maulana Nur (Program Studi Pendidikan Agama Islam, 2023)
Character education has a vital role in forming a young generation with noble character. However, after the COVID-19 pandemic, there was a decline in students' character due to the cessation of face-to-face learning. This research aims to analyze the strategies of Islamic Religious Education (PAI) teachers in developing student character at MTs Negeri 2 Cianjur. Specifically, this research identifies the methods, approaches, and activities implemented by PAI teachers to instill character values ??and evaluate their effectiveness in facing the challenges of the times. This research uses a qualitative descriptive approach with data collection techniques through in-depth interviews, participant observation, documentation, and triangulation. Primary data sources were obtained from interviews with madrasah principals, PAI teachers, and students, while secondary data came from related documents. The research results showed that PAI teachers implemented various strategies in developing student character, such as integrating religious values ??into learning and getting used to worship. , and extracurricular activities. However, there are challenges in dealing with the negative influence of digital media, which can erode noble values. This research contributes to developing a character education model that is effective and in line with the demands of the times.